Pengembangan Kinerja Karyawan PT. Erikk Kings Bersama Karawang - Adhrian Fadla Ridwan (Business and Investment Review, 2023)
Planning a development program involves determining development objectives, selecting appropriate training methods, and allocating adequate resources. Development programs can include formal training, on-the-job training, mentoring, or participation in special projects. The implementation of a development program involves providing the necessary support and facilitation for employees to participate in the program. Organizational management plays a crucial role in ensuring that employees have sufficient time and resources to participate in the development program. Employee performance evaluation is a crucial step in performance development. Evaluations can be conducted periodically to assess the extent to which the development program has improved employee performance. The results of these evaluations can be used as a basis for improving and developing more effective programs in the future. In conclusion, employee performance development is an important process in enhancing productivity and competency. With accurate needs identification, proper planning, effective implementation, and regular evaluation, organizations can create an environment that supports sustainable employee performance development ABSTRAK Perencanaan program pengembangan melibatkan penentuan tujuan pengembangan, pemilihan metode pelatihan yang sesuai, serta alokasi sumber daya yang memadai. Program pengembangan dapat mencakup pelatihan formal, pelatihan on-the-job, mentoring, atau partisipasi dalam proyek-proyek khusus. Implementasi program pengembangan melibatkan pemberian dukungan dan fasilitasi yang diperlukan bagi karyawan untuk mengikuti program tersebut. Manajemen organisasi memiliki peran penting dalam memastikan bahwa karyawan memiliki waktu dan sumber daya yang cukup untuk berpartisipasi dalam program pengembangan. Evaluasi kinerja karyawan merupakan langkah penting dalam pengembangan kinerja. Evaluasi dapat dilakukan secara periodik untuk menilai sejauh mana program pengembangan telah meningkatkan kinerja karyawan. Hasil evaluasi ini dapat digunakan sebagai dasar untuk melakukan perbaikan dan pengembangan program yang lebih efektif di masa depan. Dalam kesimpulannya, pengembangan kinerja karyawan adalah suatu proses yang penting dalam meningkatkan produktivitas dan kompetensi karyawan. Dengan identifikasi kebutuhan yang tepat, perencanaan yang baik, implementasi yang efektif, dan evaluasi yang berkala, organisasi dapat menciptakan lingkungan yang mendukung pengembangan kinerja karyawan secara berkelanjutan. Kata kunci : Pengembangan kinerja PT. Erikk kings bersama.